2002
DOI: 10.1002/aic.690480414
|View full text |Cite
|
Sign up to set email alerts
|

Feasible region for a countercurrent cascade of vapor‐liquid CSTRS

Abstract: The attainable region approach for reaction-mixing systems was applied to systems with simultaneous reaction and separation. A model de®eloped for a countercurrent cascade of two-phase CSTRs can be considered as a surrogate for the stripping or rectifying sections of a reacti®e distillation column. An o®erall composition ®ector defined satisfies the same geometric properties as the reaction ®ector. The necessary conditions for the reaction-mixing attainable region were applied to the cascade of two-phase CSTRs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 34 publications
(12 reference statements)
1
32
0
Order By: Relevance
“…They solved the problem by a constrainted optimization technique (Feinberg and Ellison, 2001;Tang and Feinberg, 2007). The AR approach is further extended by others to reactive distillation systems for some specific cases (Nisoli et al, 1997;Gadewar et al 2002;Agarwal et al, 2008a), which provided momentum for setting ideal performance targets, and gave insight into the synthesis problem by means of graphical visualization. Nisoli et al (1997) formulated a systematic approach for reactorseparator models, viz.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…They solved the problem by a constrainted optimization technique (Feinberg and Ellison, 2001;Tang and Feinberg, 2007). The AR approach is further extended by others to reactive distillation systems for some specific cases (Nisoli et al, 1997;Gadewar et al 2002;Agarwal et al, 2008a), which provided momentum for setting ideal performance targets, and gave insight into the synthesis problem by means of graphical visualization. Nisoli et al (1997) formulated a systematic approach for reactorseparator models, viz.…”
Section: Introductionmentioning
confidence: 98%
“…The extension of this approach is proposed by Chadda et al (2001) to devise basic building blocks such as co-current and countercurrent rectifying or stripping cascades with liquid or vapor removal. Gadewar et al (2002) further developed the models for a cascade of vapor-liquid CSTRs, wherein, vapor and liquid flow counter-currently to each other. They showed that the AR analysis of conventional reactor network can be conveniently extended to the reactor-separator systems.…”
Section: Introductionmentioning
confidence: 99%
“…It was further modified by Gadewar et al (2002) for the cascade of two phase CSTRs. The countercurrent cascade model of two phase CSTRs was considered as the surrogate for stripping and rectifying sections by Gadewar et al (2002).…”
Section: Introductionmentioning
confidence: 99%
“…It was further modified by Gadewar et al (2002) for the cascade of two phase CSTRs. The countercurrent cascade model of two phase CSTRs was considered as the surrogate for stripping and rectifying sections by Gadewar et al (2002). For the consecutive series reaction they showed that the suggested model offers enhanced selectivity when the reactant is heavier than the desired product.…”
Section: Introductionmentioning
confidence: 99%
“…Attainable region approach first introduced by Horn (1964) has been extensively studied and developed by Hildebrandt and co-workers (Glasser et al, 1987;Hildebrandt and Glasser, 1990;Feinberg and Hildebrandt, 1997). Further extension to this approach for the systems with reaction and separation was presented by Nisoli et al (1997), Gadewar et al (2002), and Chadda et al (2001).…”
Section: Introductionmentioning
confidence: 99%